2022
DOI: 10.1021/jacsau.2c00194
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Au–C σ-Bonds Leading to an Efficient Synthesis of [n]Cycloparaphenylenes (n = 9–15) by Self-Assembly

Abstract: The transmetalation of the digold(I) complex [Au 2 Cl 2 (dcpm)] ( 1 ) (dcpm = bis(dicyclohexylphosphino)methane) with oligophenylene diboronic acids gave the triangular macrocyclic complexes [Au 2 (C 6 H 4 ) x (dcpm)] 3 ( x = 3, 4, 5) with yields of over 70%. On the other hand, when the other digold(I) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
12
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 95 publications
3
12
0
5
Order By: Relevance
“…Über die Bildung verschiedener Ringgrößen und die geringen Ausbeuten wurde bereits häufig in anderen Beispielen der Platin‐vermittelte Makrozyklisierung berichtet [41, 42, 44, 61, 62] . Daher entschieden wir uns die Gold(I)‐vermittelte Makrozyklisierung einzusetzen und beabsichtigten zunächst eine Cyclotrimerisierungsstrategie mit dem Ziel der Bildung eines dreieckigen Makrozyklus [47, 48] …”
Section: Methodsunclassified
See 1 more Smart Citation
“…Über die Bildung verschiedener Ringgrößen und die geringen Ausbeuten wurde bereits häufig in anderen Beispielen der Platin‐vermittelte Makrozyklisierung berichtet [41, 42, 44, 61, 62] . Daher entschieden wir uns die Gold(I)‐vermittelte Makrozyklisierung einzusetzen und beabsichtigten zunächst eine Cyclotrimerisierungsstrategie mit dem Ziel der Bildung eines dreieckigen Makrozyklus [47, 48] …”
Section: Methodsunclassified
“…[41,42,44,61,62] Daher entschieden wir uns die Gold(I)-vermittelte Makrozyklisierung einzusetzen und beabsichtigten zunächst eine Cyclotrimerisierungsstrategie mit dem Ziel der Bildung eines dreieckigen Makrozyklus. [47,48] Die Reaktion von [63,64] Der innere zentrale Durchmesser von ca. 16 Å ist mit dem von [12]CPP vergleichbar und das Packungsmuster zeigt eine versetzte Stapelung einer röhrenartigen Anordnung der Ringe.…”
unclassified
“…These values are in the range as for earlier reported triangular structures and determine the hyperbolic geometry of this fourfold macro-cycle with corner angles significantly below 90°. [47,48] This demonstrates the rigidity between the two Au I centers imposed by the aurophilic interactions in this complex while flexibility originates from the [6]CMP subunits (torsional freedom around the phenyl-phenanthrenyl bonds, Figure 3a). Complex 2-Au has two chirality axes formed by the twisted Au 2 P 2 C five-membered rings of the two corners in the asymmetric unit.…”
mentioning
confidence: 99%
“…In 2020, the group of Tsuchido and Osakada reported a unique CPP synthesis via macrocyclic gold complexes. [14,15] We found that the Tsuchido-Osakada method is suitable in the synthesis of F12[6]CPP (2). Thus, (2,2',3,3'-tetrafluoro-[1,1'-biphenyl]-4,4'-diyl)diboronic acid was treated with [Au2Cl2(dcpm)] (dcpm = bis(dicyclohexylphosphino)methane) in the presence of Cs2CO3 (1:1:6 molar ratio) in toluene/ethanol/water at 50 °C to produce the corresponding hexagold(I) complex, [Au2(C6F2H2-C6F2H2)(dcpm)]3.…”
mentioning
confidence: 99%